p+-7.6=-10.7

Simple and best practice solution for p+-7.6=-10.7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for p+-7.6=-10.7 equation:


Simplifying
p + -7.6 = -10.7

Reorder the terms:
-7.6 + p = -10.7

Solving
-7.6 + p = -10.7

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '7.6' to each side of the equation.
-7.6 + 7.6 + p = -10.7 + 7.6

Combine like terms: -7.6 + 7.6 = 0.0
0.0 + p = -10.7 + 7.6
p = -10.7 + 7.6

Combine like terms: -10.7 + 7.6 = -3.1
p = -3.1

Simplifying
p = -3.1

See similar equations:

| 37-9=t+4 | | 9[x-5]=8[x+5] | | y=(1-x) | | 3H+50=8H-40 | | 3x+5=8x-49 | | 70.00+x=71.74 | | 9n-6=5n+8 | | 33x+210=11 | | 6+9=27 | | 125(y+2)=4(2y+3) | | 6(5x-7)=8(x+3) | | 3x+5+2x-9=27 | | 13x+80=11 | | 399500+387500= | | -2[r+3]=-31 | | 3[3x-2]=39 | | 4=p-9 | | 5z+10y= | | 5x-2=2x+46 | | X+64=208 | | 282000+266000= | | 3x+12+5x-2+90=180 | | 6(3x-4)+5y=-11x+13+12w | | -5(x+1)-12=15+3 | | 6(3x-4)+5=-11x+13+12w | | 3x-63+x+37=180 | | -2x+x+2(-1x+2)=x | | 7=-11+3(n+5) | | 7(n+1)=2(3-n) | | 9a^2-12a=0 | | -2x+2x+x+2(-1x+2)=x | | 8-(x+2)=12 |

Equations solver categories